PENGEMBANGAN MEDIA KADO TUTU (KARTU DOMINO TUBUH TUMBUHAN) UNTUK PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Ulya Millati, Fiqi; Mushafanah, Qoriati; Reffiane, Fine (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop KADO TUTU (Plant Body Domino Card) media in the science subject of grade IV elementary school that is feasible and practical. The type of research used is Research and Development (R&D) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. This research was conducted at SDN Bugangan 01. The results of the media expert validation test obtained a percentage of 96%, while the validation of the material expert was 96.6%, where the percentage was included in the "very feasible" category. Meanwhile, the results of the practicality test by the teacher obtained a percentage of 90.76%, then the results of the practicality test by students obtained a percentage of 99.41%, where the percentage was in the category of "very practical". Thus, the KADO TUTU (Plant Body Domino Card) media that was developed was declared very feasible and very practical to be used as a learning medium in the science subject of grade IV elementary school.